Model Pembelajaran Inovatif untuk Meningkatkan Kemampuan Menulis Permulaan Anak SD : Studi Pustaka - Ilham Gusrinand; Zaddam Riamizad; M.Haikal Haikal; Sry Apfani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to explore various innovative learning models that contribute to improving beginning writing skills in elementary school students. Using a descriptive qualitative approach through literature review, data were gathered from scientific journals, conference proceedings, and relevant academic literature published within the past five to ten years. The review findings indicate that models such as Quantum Learning, Talking Stick, and Picture and Picture are effective in encouraging active student engagement and enhancing early writing abilities. These models provide a learning environment that is enjoyable, communicative, and contextually appropriate for children's development. The study highlights the importance of employing creative and functional teaching approaches in modern elementary education. Although this research offers conceptual contributions to the development of early literacy strategies, it remains limited to literature-based findings and lacks direct field application, thus further applied research is recommended.